Hydrochemistry of the Hot Springs in Western Sichuan Province Related to the Wenchuan MS 8.0 Earthquake - Zhi Chen; Jianguo Du; Xiaocheng Zhou; Li Yi; Lei Liu; Chao Xie; Yueju Cui; Ying Li (The Scientific World Journal)
Hydrogeochemistry of 32 hot springs in the western Sichuan Province after the Wenchuan MS 8.0 earthquake was investigated by analyzing the concentrations of cation and anion and the isotopic compositions of hydrogen and oxygen. The water samples of the hot springs were collected four times from June 2008 to April 2010. Hydrogeochemical data indicated the water samples can be classified into 9 chemical types. Values of δD and δ18O indicated that the spring waters were mainly derived from meteoric precipitation and affected by water-rock interaction and mixture of deep fluids. Concentrations of K+ and SO4− of the samples from the Kangding district exhibited evident increases before the Wenchuan earthquake, indicating more supplement of deep fluids under the increase of tectonic stress. The chemical and isotopic variations of the water samples from the area closer to the epicenter area can be attributed to variation of regional stress field when the aftershock activities became weak.